Visualization Modeling of Networks Management Systems - Petryshyn, L.; Petryshyn, M.; Cieslik, W. (My University, 2020)
Simulation of the processes of sectoral cooperation management in distributed information systems allows to reduce the means of introduction and operation of such complex systems. The proposed method of visualization of information models reflects graphically the constituent processes and simplifies the understanding at the stage of analysis and design between the customer and the system developer. The basics of visualization modeling and simplified example of models development of multi-sectoral management system are presented.
Keywords: visualization modeling; information processes; sectoral cooperation; distributed systems; management